SCREENING OF RHIZOBACTERIA FROM ONION RHIZOSPHERE CAN INDUCE SYSTEMIC RESISTANCE TO BACTERIAL LEAF BLIGHT DISEASE ON ONION PLANTS - Milda Ernita, Trimurti Habazar, Nasrun Jamsari (Universitas Andalas, 2015)
In modern cultivation processes indiscriminate use of pesticides and fertilizers, has led to substantialpollution of soil, air and water. So, there is an urgent need to solve the problem. Rhizobacteria are bacteria thatcolonize plant roots, and these bacteria are known to stimulate growth and thereby reduce incidence of plantdisease by direct and indirect mechanisms. A total of 136 rhizobacteria isolates were isolated from differentrhizosphere soils in central areas of production of onions in Indonesia. These isolates were screened for theircapability to enhance growth and protect onions against bacterial leaf blight disease-caused by Xanthomonasaxonopodis pv.allii. The results showed that ten isolates can enhance growth and protect onions against bacterialleaf blight diseases. Five isolates were isolated from West Sumatra, four isolates from Java and one isolated from North Sumatra. All isolates produced indol-3-acetic acid with different concentrations. Molecular identification of ten isolates belong to Bacillus sp, Pseudomonas sp, Stenotrophomonas sp and Serratia sp.